The Misuse of Social Media as a Means of Electronic Transactions in the Ambon Class I Type a Navigation District - Rusly Karim; D. J. A. Hehanussa; Elsa R. M. Toule (Riviera Publishing, 2026)
This study discusses the misuse of social media as a means of illegal electronic transactions in the Ambon Class I Type A Navigation District, particularly in relation to cyber fraud and identity abuse in the digital era. The research aims to analyze the forms of social media misuse, identify the modus operandi used by perpetrators, and evaluate the effectiveness of law enforcement against cybercrime involving government institutions. This research employed a normative juridical method using statutory, conceptual, and case approaches. Primary legal materials included the Indonesian Electronic Information and Transactions Law, the Criminal Code, and the Personal Data Protection Law, while secondary materials consisted of journals, books, and relevant legal documents. The findings reveal that the primary form of abuse involved fictitious PPPK recruitment fraud through fake social media accounts, falsified electronic documents, phishing practices, and manipulation of institutional identities, resulting in significant financial losses for victims. The study also found that law enforcement remains ineffective due to limitations in digital forensic infrastructure, difficulties in identifying anonymous perpetrators, weak coordination among institutions, and low public digital literacy. Furthermore, the absence of verified official social media accounts increased the vulnerability of institutional identity misuse. The study concludes that although Indonesia has adequate legal regulations to address cybercrime, effective law enforcement requires stronger digital infrastructure, improved investigative capacity, verified digital communication channels, and greater public awareness regarding cyber fraud prevention.